2019
DOI: 10.3892/ijmm.2019.4435
|View full text |Cite|
|
Sign up to set email alerts
|

Cancer‑related fatigue during combined treatment of androgen deprivation therapy and radiotherapy is associated with mitochondrial dysfunction

Abstract: combined androgen deprivation therapy (AdT) and radiation therapy (RT) is the standard of care treatment for non-metastatic prostate cancer (NMPC). Despite the efficacy, treatment-related symptoms including fatigue greatly reduce the quality of life of cancer patients. The goal of the study is to examine the influence of combined ADT/RT on fatigue and understand its underlying mechanisms. A total of 64 participants with NMPc were enrolled. Fatigue was assessed using the Functional Assessment of cancer Therapy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 58 publications
(52 reference statements)
2
26
0
Order By: Relevance
“…Whole extracted brains were flash-frozen in liquid nitrogen. Lysates were made in the same manner as previously reported [23]. The samples were denatured at 100˚C for 5 minutes and loaded onto 4-20% Mini-PROTEAN 1 TGX™ Precast Gels (Bio-Rad, Hercules, CA, USA).…”
Section: Bdnf Western Blotmentioning
confidence: 99%
“…Whole extracted brains were flash-frozen in liquid nitrogen. Lysates were made in the same manner as previously reported [23]. The samples were denatured at 100˚C for 5 minutes and loaded onto 4-20% Mini-PROTEAN 1 TGX™ Precast Gels (Bio-Rad, Hercules, CA, USA).…”
Section: Bdnf Western Blotmentioning
confidence: 99%
“…In fact, mitochondrial dysfunction is often secondary to a disruption of carnitine homeostasis (Sharma and Black, 2009). ADTinduced changes in metabolites related to carnitine synthesis and mitochondrial fatty acid oxidation may help explain our previous observation of mitochondrial dysfunction in fatigued patients (Feng et al, 2020). Another pathway of interest that was associated with metabolites that significantly discriminated between the two groups was glutathione metabolism (Figure 1E), including cysteinylglycine and oxidized cys-gly (Figure 3B).…”
Section: Discussionmentioning
confidence: 75%
“…The underlying mechanism remains poorly understood. Feng et al [27] showed that combination ADT and radiation therapy worsened fatigue and was associated with anemia and mitochondrial dysfunction. By contrast, Bandara et al [28] used multivariate models with fatigue as the outcome and found that neither hemoglobin nor T levels had a significant within-patient effect on fatigue developing during ADT/radiation therapy.…”
Section: Discussionmentioning
confidence: 99%